I sacrifici e la loro funzione conoscitiva in Filone di Alessandria - Calabi, Francesca 1948- (2001)
For Philo, the language of sacrifices is one that can be interpreted and clarified through an allegorical reading. A philosophical and cognitive role is attributed to the cult, whether it is sacrificial, prayer, or study. There is no opposition between the various cult forms as they appear side by side, without rejecting that there is no opposition between sacrifice as a concrete cultic act and sacrifice in its symbolic meaning. Closely connected to the previous subject is the connection of the Temple of Jerusalem to practical necessities and functions of unity and cohesion, and the relation between the Temple of Jerusalem and a cosmic temple.
Keywords: Philo -- Alexandrinus -- v25-40; Opfer